Keadilan Restoratif Dan Pembatasan Diversi Pada Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak - Dewantary, Zenny Rezania (Veritas et Justitia, 2016)
AbstractSince 1997 Indonesia possessed a Law specifically regulating child court (Law No. 3 of 1997). The law’s perspective, however, was still based on retributive justice. This was apparent in how the court handles juvenile delinquents.  To provide better protection to the handling of children before criminal courts, the government amended Law No. 3 of 1997 by Law No. 11 of 2012 re. Juvenile Court System. This new law was founded upon the theory of restorative justice and provide for diversion.  Diversion is used to prevent children from being sent to prison and in general purports to improve societal condition. This article discusses problems related to the use of diversion. One recommendation offered is that diversion should be taken into consideration without discrimination, not only in the case the penal sanction is below 7 years (imprisonment) but also above this number. In deciding the need for diversion, while also taking into consideration the seriousness of the crime committed, expediency should also be a deciding factor.